Identifikasi Risiko pada Rekam Medis Elektronik Rawat Inap Menggunakan Metode FMEA di Rumah Sakit Islam Banjarmasin - Rizqi Aulia Husna; Eka Rahma Ningsih (UPPM Politeknik Unggulan Kalimantan, 2024)
Electronic medical records that occur are a threat to hospitals, because they can cause problems with electronic medical records. The purpose of this study was to identify the risks in the inpatient electronic medical records using the FMEA method at the Islamic Hospital of Banjarmasin. This research method uses quantitative. The risk of incomplete data on inpatient electronic medical records using the FMEA method at Banjarmasin Islamic Hospital can find out failures that occur by calculating the RPN in the NIK section with a score of 270 in the high category, Name with a score of 81 in the very low category, Age with a score of 42 very disturbing, and Address a score of 30 is very annoying. This occurs because there is no SOP regarding data completeness, and there is no system that can control when the patient's identity is not filled in completely in the inpatient electronic medical record. The risk of inaccuracy of data in the inpatient electronic medical record using the FMEA method at Banjarmasin Islamic Hospital can identify failures that occur by calculating the RPN in the NIK section with a score of 900 in the very dangerous category, Name score 90 in the very low category, Age score 35 slightly disturbing, and Address score 25 is a bit annoying. This occurs as a result of the absence of an SOP regarding data accuracy, and the absence of a system that can recognize when the patient's identity is incorrect or the need for quantitative analysis to find out inaccurate data in the inpatient electronic medical record. The risk of data duplication in the inpatient electronic medical record using the FMEA method at Banjarmasin Islamic Hospital can find out failures that occur by calculating the RPN in the NIK section with a score of 270 in the high category, Name score 243 in the medium category, Age score 54 in the low category, and Address score 54 with low category. This happens due to the absence of an SOP regarding duplication of data, and the absence of a support system when inputting data that fails to be stored, so it cannot be re-entered. In order to avoid duplication of data in the inpatient electronic medical record.